PENGOLAHAN AIR GAMBUT UNTUK PERSEDIAAN AIR BERSIH - Perpustakaan UGM, i-lib ([Yogyakarta] : SekolahPascasarjana Universitas GadjahMada, 2000)
ABSTRACT An alternative raw water resource used to fulfill freshwater need in Pontianak Municipality is the organic colored water (locally known as peat water). The main problem using peat water is its low-pH, brownish in color, high organic content, high iron (Fe) content, and turbidity. One of the efforts to decrease these drawbacks is to treat the peat water using coagulants (natural coagulant and supplement coagulant, i.e. kelor seeds, clay and lime). The treatment is based on coagulation-flocculation process. The aims of peat water treatment using the coagulant, are